Microsoft Surface Hub 2S : the higher-education market opportunity - Sawhney, Mohanbir S.; Goodman, Pallavi (London : Kellogg School of Management, 2021)
The Surface Hub 2S, a video-based collaboration device, had been initially designed for the corporate market. In late 2020, Jon Worsley, senior director of hardware program management at Microsoft, and Frank Buchholz, senior product marketing manager for Surface devices, were exploring a new opportunity in the higher-education market. In the wake of the coronavirus pandemic, Zoom had established itself as the go-to software platform for livestreaming and webinars for higher education. Worsley and Buchholz believed that the Surface Hub, with its large display and Microsoft Teams collaboration software, could offer a more powerful integrated solution for teaching and learning for universities and colleges. To pursue the higher-education market opportunity, Microsoft would need to pivot the positioning and messaging, as well as the design of the Surface Hub 2S. This pivot involved two sets of decisions: one in marketing communications and the other in product design. In the short term, Microsoft's marketing team, led by Buchholz, would need to redesign the value proposition, positioning, and messaging for the Surface Hub to appeal to educators. In the longer term, Worsley's engineering team would need to redesign the product features and the product architecture of the Surface Hub 2S to better address the needs of students and instructors. In entering the higher-education opportunity, Microsoft had to be careful not to create a product or deliver a message that would diminish its offering for the core corporate market.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Product management -- Case studies; Marketing -- Management -- Case studies; Product design -- Case studies